Attention-driven demand for bonus contracts - Markus Dertwinkel-Kalt; Mats Köster; Florian Peiseler (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
In many markets supply contracts include a series of small, regular payments made by consumers and a single, large bonus that consumers receive at some point during the contractual period. But, if for instance its production costs exceed its value to consumers, such a bonus creates inefficiencies. We offer a novel explanation for the frequent occurrence of bonus contracts, which builds on a model of attentional focusing. Our main result identifies market conditions under which bonus contracts should be observed: while a monopolist pays a bonus to consumers, if at all, only for low-value goods, firms standing in competition always - i.e., independent of the consumers' valuation - offer bonus contracts. Thus, competition does not eliminate but rather exacerbates inefficiencies arising from contracting with focused agents. Common contract schemes in markets for electricity, telephony, and bank accounts are consistent with our model, but cannot be reconciled with alternative approaches such as models on consumption smoothing, (quasi-)hyperbolic discounting, or switching costs.
Keywords: D91; D18; D40; L10; 330; Attention; Focusing; Bonus Contracts